2014
DOI: 10.1590/s1984-29612014046
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of immature forms of culicids (Insecta: Diptera) in the northeastern region of Brazil

Abstract: The Culicidae family is represented by approximately 3,610 species, among which many are involved in transmission of pathogens and parasites, thus presenting great medical-veterinary importance. In Brazil, the state of Pernambuco is considered an endemic area for many diseases vectored by mosquitoes, such as human and canine filariasis, caused by Wuchereria bancrofti and Dirofilaria immitis, respectively. The aim of this study was to evaluate the occurrence of immature forms of culicids, over an one-year perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Additionally, we found that T. mauritanica is feeding on Culex theileri, a mammophilic mosquito, widely distributed across Europe, North Africa, and southwest Asia and vector for several zoonotic diseases (Demirci et al, 2012). This species is a competent vector of human and domestic animal pathogens, caused by Wuchereria bancrofti (main cause of lymphatic filariasis) and Dirofilaria immitis (the dog heartworm), respectively (Demirci et al, 2012(Demirci et al, , 2014Silva et al, 2014). In fact, C. theileri is likely the main vector of the dog heartworm disease in Madeira, which is estimated to affect 30% of the island's canines (Clemente, 1996;Santa-Ana et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, we found that T. mauritanica is feeding on Culex theileri, a mammophilic mosquito, widely distributed across Europe, North Africa, and southwest Asia and vector for several zoonotic diseases (Demirci et al, 2012). This species is a competent vector of human and domestic animal pathogens, caused by Wuchereria bancrofti (main cause of lymphatic filariasis) and Dirofilaria immitis (the dog heartworm), respectively (Demirci et al, 2012(Demirci et al, , 2014Silva et al, 2014). In fact, C. theileri is likely the main vector of the dog heartworm disease in Madeira, which is estimated to affect 30% of the island's canines (Clemente, 1996;Santa-Ana et al, 2006).…”
Section: Discussionmentioning
confidence: 96%